Digital Literacy Enhancement for Expanding the Market Reach of Fishermen in Kilang Village - Paskanova Christi Gainau; Fanny Monica Anakotta; Zalni Zalni; Christy Clayde Latupeirissaa (Ali Institute of Research and Publication, 2026)
Traditional fishermen are micro-scale enterprises with the potential to absorb labor and reduce poverty in coastal areas. However, they often face several challenges, such as low sales turnover that is not proportional to operational costs, limited innovation in marketing strategies, and the long distance to traditional markets. These conditions are also experienced by fishermen in Kilang Village, Leitimur Selatan District, Ambon City. Therefore, this community service activity aims to improve fishermen’s digital literacy in order to expand market reach through the use of digital technology. The implementation method includes an initial survey and problem mapping, administration of a pre-test, socialization and discussions on the digitalization of fish markets, and a post-test to evaluate participants’ improved understanding. The activity was conducted from March 23 to 25, 2025, at the Kilang Village Office and involved 27 local fishermen. A descriptive quantitative method was used to analyze pre-test and post-test data to assess changes in participants’ level of understanding. The results indicate an increase in participants’ understanding of the use of digital platforms for marketing fishery products, as shown by the increase in the average score from 40 in the pre-test to 80 in the post-test. These findings suggest that digital literacy can serve as an initial step in encouraging fishermen to adopt digital markets, thereby improving marketing efficiency, expanding market access, and supporting the sustainability of fishing businesses in coastal areas.